A new approach to determine suitable heating parameters for hull plates formed by torch line heating - Tran, Thai Gia; Huynh, Chinh Van (Journal of Naval Architecture and Marine Engineering, 2021)
In shipbuilding, the process of forming flat metal plate into curved hull plates with compound shapes is very important and has greatly affected many economic and technical factors such as strength, quality, and aesthetics of the hull, construction cost and time, etc. Currently, the forming method of curved hull plates by line heating is used effectively and commonly in many shipyards, however, its main problem is very difficult to determine where and how much to heat on the flat metal plate to obtain the plate of a certain shape. In this article, a finite element model is established and adjusted based on the actual data to numerical simulate the process of forming hull plates by using flame torch line heating. Base on this, the suitable position and temperature for the heating lines in the forming process are determined to form a metal plate into hull plates with the exact desired shapes. This research has been applied for forming by torch line heating of two plates, denoted K1 and K10, in the bulb bow of a 20,000 DWT cargo ship, built at Camranh Shipyard in Vietnam with the deformation deviations between the actual and desired plate surfaces are within ± 3%.